Inovasi Karakteristik Produk Souvenir Bambu Laminasi Sebagai Upaya Pengembangan Teknologi Pembuatan Souvenir yang Ekonomis dan Ramah Lingkungan - Bhakti Jayadi; Wahyullah Wahyullah; M. Fadli Alamsyah; Suhasman Suhasman (Hasanuddin Student Journal, 2017)
Bamboo plants have long been known as the raw material for souvenir products, but the diversity of bamboo products is limited to the basic shape of the cylinder, the segments, and the hollow. Application of lamination technology is useful to shape bamboo as desired. Laminate bamboo technology has been widely developed, but limited to the purpose of construction and furniture. However, the use of technology for souvenir purposes remain limited. This research is conducted to identify the characteristics of souvenir products made from raw laminated Petung bamboo. Petung (Denrocalanus asper) is chosen because the blade is thick and the diameter is relatively large compare to other bamboo species. This type of souvenir product used in this research is board and beam based. Identification of product characteristics is done by qualitative method (interview) and quantitative (observation of defective products). Souvenir products made from raw bamboo laminate tend to have a higher aesthetic value than solid wood products. The results showed that the average defect-free value of souvenir products was 66%, and included in defect-free class II, with good machining quality. Of the 30 respondents interviewed related to the perception of bamboo laminate products, 53% of respondents said the type of product is interesting, while 36% said very interesting. On the scale of 1-10, most of the respondents choose 8 and 9. It indicates that the uniqueness, function, and distinctiveness of the product are important for the respondents. The additional future such as better shape and function adjustment, and improved finishing quality will further enhance consumer interest in bamboo laminate souvenir products.Keywords: Bamboo, Characteristics, Laminate, Souvenir.